Edukasi Gizi Seimbang sebagai Upaya Pencegahan dan Penatalaksanaan Gizi Kurang pada Balita - ravimasitah; Safrida; Fanany , Irzal; Dessritina, Pesona (Pusat Pengembangan Pendidikan dan Bakat Indonesia/Education and Talent Development Center of Indonesia, 2025)
Nutritional issues in toddlers remain a serious challenge in Indonesia, particularly in Aceh Province and West Aceh Regency, where the prevalence is higher compared to the national figures. Malnutrition during the first 1000 days of life can lead to long-term effects such as stunted growth, decreased learning abilities, and increased risks of morbidity and mortality. Nutritional education efforts through counseling and outreach are necessary to improve mothers' knowledge and nutritional behavior. Outreach was conducted for 57 mothers using PowerPoint media, while counseling was provided for 4 undernourished toddlers through home visits. Evaluation was conducted using pre-tests and post-tests. The results showed that outreach improved understanding of balanced nutrition, risk factors, and prevention of malnutrition. Counseling significantly improved mothers' knowledge scores, from an average of 37.5 to 87.5. It can be concluded that nutrition education effectively encourages changes in knowledge and behavior, thus it needs to be implemented continuously.